Tuberculosis Suspect in the Companies in Semarang District Indonesia; Case-Control Study - Rahayu, Sri Ratna; Katsuyama, Hironobu; Katsuyama, Midori; Ota, Yoko; Djaja Semadi, Ngakan Putu (Jurnal Kesehatan Masyarakat, 2017)
In Semarang district, the population at the companies were 83120 workers. The number of smear positive cases in 2011 were 258 and 3898 suspected tuberculosis. Case-control study was conducted to analyze the risk of TB suspect infection among workers in the factory. We recruited 194 suspects and 197 controls who visited the factory clinic. The most common symptom was coughing with sputum (63 %) and then followed by malaise, chest pain, sweating at night, weight loss, dyspnea, anorexia, cough more than 2 weeks, sub febris and hemoptoe. Around 47 % both of the suspects and controls donât know received Bacillus Calmette-guérin (BCG) or not. The multivariate analysis showed the dominant factors that influence the occurrence of TB suspect, âeducationâ, âincomeâ, âashamed of having TBâ, âTB treatment is very costlyâ, and âshare dishâ.distribution of health education booklet to teachers and parents.